Univariate or multivariate analysis for better prediction accuracy? A case study of heterogeneity in vehicle ownership. Issue 8 (14th September 2018) - Anowar, Sabreena; Eluru, Naveen
ABSTRACT: We contrast different modeling frameworks that offer alternative ways of capturing observed/unobserved heterogeneity. The model systems compared are: ordered logit, residential location cluster-based ordered logit model (exogenous segmentation), mixed ordered logit, latent segmentation-based ordered logit model, and a joint copula-based self-selection clustering model. While the comparison across single dependent variable models is straight forward, the comparison with the copula-based model requires post-processing to generate marginal distribution for the choice of interest. The comparison exercise is conducted in the vehicle ownership context using O–D survey data of Greater Montreal Area, Canada. The superior performance of the ordered part of the joint copula-based model in the context of model estimation and validation indicates that employing information from an additional dependent variable (such as residential location choice in our case) allows us to better understand and predict the main dimension of interest (vehicle ownership).